2022
DOI: 10.1155/2022/7928052
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring the Clinical Point Selection Rules of Acupuncture and Moxibustion in the Treatment of Infantile Enuresis Based on Data Mining Technology

Abstract: In order to explore the clinical point selection rules of acupuncture and moxibustion in the treatment of infantile enuresis based on data mining technology, first, it introduces the principle of data mining technology, the global optimization strategy of information extraction + genetic search. In China Biomedical Literature Database, CNKI, Weipu, Wanfang. Use “enuresis,” “enuresis,” “leathering,” “urinary discharge,” “drowning,” “bedwetting,” “nocturia,” “drowning,” “moxibustion,” “moxibustion,” and “moxibus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%